Ethical dilemmas as professional challenge : case study on management in reception centers in Finland - Okkonen, Ida (2017)
This study examined what kinds of ethical dilemmas managers working in reception centers in Finland have encountered as well as what kinds of strategies they applied in ethically challenging situations, and finally, what ethical dimensions the strategies included. This specific topic has not been investigated before, thus, this study aimed to theoretically and empirically examine it. Theoretical framework bases on Geva’s (2006) typology of ethical dilemmas, Jones’ (1991) issue- contingent model of moral intensity, and Rahim & Bonoma’s (1979) model of the styles of handling interpersonal conflict. The study is qualitative in nature, and was conducted by interviewing ten (10) managers working in reception centers in Finland. Interviews were semi-structured thematic interviews where a critical incident technique had a vital role (Flanagan, 1954). The results revealed that most of the interviewed managers encountered ethical dilemmas that were related to termination of reception services, as only one manager’s ethical dilemma was related to termination of employment relationship. One manager had not encountered any ethical dilemmas, thus, termination of reception services had evoked some kind of ethical pondering. Moral intensity was found to be influencing ethical evaluation and ethical decision making. Furthermore, most of the managers did not seem to struggle with interpersonal ethical conflicts, but rather with general policies against governmental institutions. Managers’ ethical decision making revealed four applied strategies: obliging, compromising, principled, and teaching. Furthermore, the applied strategies included ethical features from act and rule deontology and act utilitarianism, consequentialism, as well as from virtue ethics and ethics of care. Lastly, the compromising strategy seemed to be applied by most of the managers.